Least-Cost Formulation Of Feeds For Prawns, With Particular Reference To Macrobachium Rosenbergii (De Man) - Poh, Yong Thong (1985)
Linear programming was used in least-cost formulation of feeds for Macrobrachium rosenbergii. The constraints were : crude fat of 5 to 10% , gross energy of 4 , 400 cal/g, an amino acid profile similar to that of the prawn and specified amounts of crude protein of either 25% , 30% , 40% or 50% . Four pellets , P . 25 , P . 30 , P . 40 , and P . 50 , were formulated , costing M$0.72, M$0.75 , M$0.8l and M$l.04 per kilogram respectively .Chemical analyses indicated that the crude protein , crude fat and gross energy content of the formulated feeds agreed closely with the given constraints . Amino acid analyses showed that the amino acid profiles (with the exception of tryosine , leucine and lysine ) of the formulated feeds were remarkably similar to the amino acid profile of the prawn .Three culture systems were designed to maintain optimal physico-chemical conditions for testing the responses of the prawn to the pellets . P . 40 was shown to produce a higher growth rate of 1.15 em per month for postlarval M. rosenbergii ( 0 . 96 3 . 08 em post-orbital length ) and 1 . 02 em per month for juvenile M. rosenbergii ( 2 . 67 - 4 . 64 em post-orbital length ) . The results indicated that the optimum protein level of the diet formulated by linear programming for best growth was 40% .